Use of open software for information literacy in academic libraries: issues and challenges - Abd Samad, Zaharah; Hazmi, Norzelatun Rodhiah (2015)
One of the ways to sustain the relevancy of libraries in this electronics era is to prove its stakeholders that a library is still very much useful for acquiring knowledge and virtues. Librarians in Malaysia, specifically in academic libraries, have been initiating proactive approaches in marketing library services & resources for users to access it in a more efficient and effective way. One of the approaches done is by conducting information literacy workshop to educate them on how to use the library online resources, i.e. online databases and e-books, as well as on how to locate physical materials in the library premise. This study is conducted to address current issues and challenges faced by the librarians while using ‘zero cost’ open software as a tool for interactive teaching, evaluating performance and registration process for information literacy workshop. It is also done to explore on which open software that are currently use for their information literacy workshop. From this point, a list of open software that is/are commonly used by these academic libraries is revealed. A survey is distributed to a group of librarians from selected public and private universities to gather the information. Based on the analysis, the most feasible and reliable open software for information literacy is recommended.